Pengaruh Lingkungan Kerja, Beban Kerja , dan Gaya Kepemimpinan terhadap Kepuasan Karyawan: Studi pada Karyawan Marketing Gallery Graha Raya PT Jaya Real Property Tbk - Feriansyah Fauzi; Syaiful Anwar (JURNAL RISET MANAJEMEN (JURMA), 2025)
This research aims to analyze the impact of the Work Environment, Workload, and Leadership Style on Employee Satisfaction at Marketing Gallery Graha Raya PT Jaya Real Property Tbk. The study employs a non-probability sampling method with a saturated sampling approach, involving 39 employees from the company as respondents. Data analysis was conducted using multiple linear regression with the aid of SPSS version 25. The findings reveal that Work Environment and Workload do not significantly affect Employee Satisfaction, whereas Leadership Style has a positive and significant impact. Collectively, these three variables contribute 74.9% to Employee Satisfaction, leaving 25.1% influenced by other factors. The outcomes of this research serve as a valuable reference for companies in developing more effective HR policies to enhance employee motivation and productivity by improving job satisfaction.